2021
DOI: 10.1155/2021/5568113
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Key Signaling Pathways Associating miR-204 and Common Retinopathies

Abstract: MicroRNAs are a large group of small noncoding RNAs that work in multiple cellular pathways. miR-204, as one of the key axes in the development, maintenance, and pathogenesis of the retina, plays several roles by modulating its target genes. This study was aimed at evaluating the target genes of miR-204 involved in the development and progression of common retinopathies such as glaucoma, retinoblastoma, and age-related macular degeneration. In this study, three datasets related to retinopathies (GSE50195, GSE2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
0
6
0
1
Order By: Relevance
“…In this way, miR-204 performs critical functions during retinal development and maintenance. 28 , 29 The aberration of miR-204 may reflect the irreversible changes of the retina.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, miR-204 performs critical functions during retinal development and maintenance. 28 , 29 The aberration of miR-204 may reflect the irreversible changes of the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Rb have survival rates higher than 95-98% in industrialized countries but mortality remains high in developing countries ( 2 , 4 , 12 ). For example, the mortality rate in Africa is 70% ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…This increase in proliferation is linked to the miR-17 sub-family, which targets cell-cycle inhibitors p21 and p57 ( 43 ). miR-204 acts as a tumor suppressor, while it has much less expression in patients with retinoblastoma ( 44 ). Cyclin-D2 and MMP-9 are two key genes that are regulated by miR-204 in retinoblastoma.…”
Section: New Treatment and Diagnostic Perspectives Of Retinoblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the expression of miR-204 in Rb patients is dysregulated, and its expression level is related to optic nerve infiltration, lymph node metastasis, and tumour tissue differentiation. miR-204 may affect the proliferation and apoptosis of Rb cells, thereby affecting the development of Rb, which may become an early stage molecular indicator for diagnosing and evaluating the prognosis of Rb (43)(44)(45); miR-338-5p is up-regulated in the serum of patients with Rb, which may play a role in promoting cancer in the occurrence and development of Rb, and has the potential value of the early diagnosis of Rb (46,47). Recent studies have shown that dysregulated miR-592 and miR-217-3p have been reported to be involved in developing many different types of cancer.…”
Section: Discussionmentioning
confidence: 99%